KARAKTERISTIK PENDERITA DIABETES MELITUS TIPE 2 DENGAN COVID-19 DI RUMAH SAKIT UMUM Prof.Dr. I.G.N.G NGOERAH - IDA BAGUS ADITYA NUGRAHA; WIRA GOTERA; RIONALDO ANTHONIUS (Ganesha Medicina, 2022)
Abstract Introduction: COVID-19 is caused by a novel coronavirus known as SARS-CoV-2, a single chain RNA virus with a particle size of 120-160 nm. COVID-9 can affect almost all age groups, despite, the elderly and people who have records of chronic disease (co-morbid) have the risk to be affected more often and with worse complications from this disease. Type 2 Diabetes mellitus (DM) is one of the risk factors for enhancing the severity of COVID-19 infection Method: This study is a descriptive study with cross-sectional approach. Sampling with consecutive sampling. This sampling was done from Januari 2021 until April 2021. Analysis done with SPSS application. Results: From 57 patients, 54.4% was male vs 45.6.7% was female. 43.9% was above 60 years old vs 56.1% was below 60 years old. 17.1% with insulin regimen vs 82.9% oral diabetic drug. 60.4% with overweight BMI vs 39.4% normal BMI. 7% with below 6.5 Hba1c vs 93% above 6.5 Hba1c. 51.4% patients more than 5 years duration of diabetes vs 40% over 5 years and 8.6% over 10 years.1.8% patients with moderate COVID-19 vs 38.6% Severe COVID-19 vs 59.6% with Critical Ill COVID-19. Conclusion: from this study, we can learn the characteristic Type 2 Diabetes Melitus patients with COVID-19. Factors like age, gender, A1c level, duration of diabetes, were associated with severity of COVID-19. However, this study has a lot of weakness from methods, analysis and sampel similarity. We hope that another study can be better method than this study. Keywords: diabetes, covid 19 infection, complication